Properties of different TIG coatings of Stellite on the Hardox 450 and St 52 steel - Kirik, Ihsan; Zulkuf Balalan; Imak, Anil; Yaz, Mehmet (Carl Hanser Verlag, 2020)
The aim of this study was to coat different types of Stellite (1, 6 and 12) whose carbon rates vary on Hardox 450 and St 52 steel by means of tungsten inert gas (TIG) welding. For the purpose of microstructure investigations after welding, SEM, EDX, X-Ray and microhardness tests were carried out. It was observed that different types of Stellite coating with different features have an effective influence on microstructure and in the presence of dendritic nets between the grains decreased when the carbon content in Stellite coating decreased and when the substrates varied. In addition, it was determined in microhardness examinations that hardness increased with increasing carbon content and that the highest hardness value of 762 HV in sample S1 was attained. Consequently, positive results have been given for coating Hardox 450 steel and St 52 steel with Stellite via the TIG method.
Keywords: Hardox 450; St 52; stellites 1, 6 and 12; tungsten inert gas welding